Mechanical and Corrosive Nature of Galvanized Steel in Sodium Chloride Solution - Chowdhury, Azrin Akhter; Aisyah, Iis Siti (Journal of Energy, Mechanical, Material and Manufacturing Engineering, 2018)
Galvanizing also denoted as zinc coating is a scientifically approved method applied to protect iron and steel against the effects of corrosion. In the galvanization process, aluminum is added with zinc. Zinc has numerous properties under different environmental conditions. These properties are subject to change when it comes to the coating process. The common properties here may include its appearance, hardness, the thickness along with other mechanical and physical properties. Due to these properties, there may also be inconsistency on the coating structure. So the addition of aluminum unto zinc, will ensure that various properties are eliminated for the better improvement of the zinc coating process. Aluminum possesses stronger mechanical properties and therefore valid for the coating process. It ensures that zinc is not arrived at by the corrosion agents. In this study, the focus will largely be based on the impact of aluminum on corrosion behavior as aligned to hot-dip galvanized steel. However, in this study, the galvanization process was performed using the dry process. The percentage variation of zinc resulted in different results in the rate of corrosion. The hardness of zinc thus increased via additional of aluminum percentage.